Meningkatkan kualitas kepala sekolah diera digital: Studi kasus pencurian di Madrasah Ibtidaiah Pirang - Ali, Abd Adiem Radif; Nafisah, Jauharatun Nafisah; Muttaqin, M. Imamul Muttaqin Imamul; Jauhar, Roja Fadla MOH. (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of school principals' leadership in improving performance quality in educational environments, particularly in addressing the challenges of the digital era. School principals play a central role in managing schools, enhancing the quality of educators, and implementing effective managerial strategies. This research employs a qualitative method with a literature review approach, examining various studies related to leadership, performance, and education quality. The findings indicate that effective leadership is determined by decision-making abilities, strong communication, and innovation in utilizing technology to improve school management. A case study on theft at MI DDI Pinrang highlights the importance of digital security systems in safeguarding school assets. The proposed solutions include cloud-based CCTV systems, digital asset management systems, and increased security awareness among the school community. By adopting adaptive and technology-based leadership strategies, school principals can create a safe, conducive, and high-quality learning environment.